Light collection simulation when determining light yield of single crystal and polycrystalline organic scintillators - Gorbacheva, T.E.; Tarasov, V.A.; Galunov, N.Z. (Functional Materials, 2015)
The light-collection coefficients were calculated for different scintillation detectors using discrete optical model. Сharacteristics of optical media, which cannot be measured directly, were fitted using experimental response of scintillation materials with different light collection conditions. Using proposed technique absolute light yield (ALY) of single crystal, composite and polycrystalline scintillators on the base of stilbene, anthracene, pure and doped p-terphenyl were determined. Average ALY values obtained in this study are similar to the results for the single-crystal samples.